Comparative safety and efficacy of percutaneous radiofrequency thermocoagulation and percutaneous balloon compression in CT-guided and local anesthesia for recurrent trigeminal neuralgia - Xi, Lulu; Liu, Xiaohui; Shi, Hongchen; Han, Wenbiao; Gao, Liqin; Wang, Li; Liu, Junpeng; Ren, Yue; Du, Yuanyuan; Liu, Guangzhao (Frontiers in Neurology, 2024)
Background There are several ways to treat trigeminal neuralgia (TN); however, TN may recur after treatment. Although microvascular decompression (MVD) is considered an effective treatment for trigeminal neuralgia, patients with recurrence may not be willing to undergo craniotomy. Objective This study compared the safety and efficacy of percutaneous radiofrequency thermocoagulation and percutaneous balloon compression for treating recurrent trigeminal neuralgia. Methods This was a prospective non-randomized controlled study. A total of 52 with recurrent TN were scheduled to undergo surgery in our Hospital from January–June 2021. The patients were classified into percutaneous radiofrequency thermocoagulation (PRT) and percutaneous balloon compression (PBC) groups based on the treatment. All surgeries were performed under computed tomography guidance and local anesthesia. Post-operative complications were also observed. Pain was assessed using the visual analog scale (VAS) and Barrow Neurological Institute (BNI) scale. Efficacy indices were evaluated at 3, 6, 12, and 18 months after surgery. Results During follow-up, the efficacy rates of the two methods within 18 months were 76.0 and 88.9%, respectively. All patients had hypoesthesia on the affected side, and no severe complications. Notably, 5 patients (20%) in the PRT group with multiple-branch pain, including the first branch of the trigeminal nerve (V1) pain in the PRT group, received radiofrequency therapy for the supraorbital notch (foramen) after puncture of the foramen ovale. However, multiple pain episodes resolved with only one operation in the PBC group. Conclusion CT-guided percutaneous radiofrequency thermocoagulation and percutaneous balloon compression under local anesthesia may be good options for treating recurrent trigeminal neuralgia. Percutaneous balloon compression may be recommended when multiple branches are involved, particularly in cases of V1 neuralgia.